Pengaruh Penggunaan Artificial Intelligence terhadap Berpikir Kritis dengan Literasi Digital sebagai Variabel Mediasi Siswa di Era Society 5.0 - Julia Risky Handayani; Marsofiyati Marsofiyati; Maulana Amirul Adha (Jurnal Pendidikan dan Kebudayaan (JURDIKBUD), 2026)
The development of artificial intelligence technology in education has driven changes in student learning patterns, particularly in accessing and processing information. In vocational high schools, the use of Artificial Intelligence (AI) is increasingly common to assist with task completion and reference searches. However, its effectiveness is greatly influenced by students' level of digital literacy so that the technology can be used critically, selectively, and responsibly. This study aims to analyze the effect of AI use on students' critical thinking skills with digital literacy as a mediating variable. The approach used is quantitative with a survey method. The research population includes all 819 students of SMK Negeri 45 Jakarta, while the accessible population focuses on 216 students with expertise in Office Management. A sample of 135 respondents was determined using probability sampling with proportionate random sampling based on grade level. The data were analyzed using Partial Least Squares based Structural Equation Modeling (SEM-PLS) through the SmartPLS 4.0 application, which included testing the measurement model, structural model, and hypothesis testing to see the direct and indirect relationships between variables. The results showed that the use of AI had a positive and significant effect on critical thinking skills. Digital literacy also has a positive influence on critical thinking and is positively related to AI use. In addition, digital literacy has been shown to mediate the relationship between AI use and critical thinking skills. These findings imply that optimizing the use of AI in learning needs to be accompanied by strengthening digital literacy in order to improve the quality of students' critical thinking skills more effectively and sustainably.